FOXO1 promotes resistance of non-Hodgkin lymphomas to anti-CD20-based therapy. (4th May 2018) - Pyrzynska, Beata; Dwojak, Michal; Zerrouqi, Abdessamad; Morlino, Giulia; Zapala, Piotr; Miazek, Nina; Zagozdzon, Agnieszka; Bojarczuk, Kamil; Bobrowicz, Malgorzata; Siernicka, Marta; Machnicki, Marcin M.; Gobessi, Stefania; et al.
ABSTRACT: Diminished overall survival rate of non-Hodgkin lymphoma (NHL) patients treated with a combination regimen of rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP) has been recently linked to recurrent somatic mutations activating FOXO1. Despite of the clinical relevance of this finding, the molecular mechanism driving resistance to R-CHOP therapy remains largely unknown. Herein, we investigated the potential role of FOXO1 in the therapeutic efficacy of rituximab, the only targeted therapy included in the R-CHOP regimen. We found CD20 transcription is negatively regulated by FOXO1 in NHL cell lines and in human lymphoma specimens carrying activating mutations of FOXO1 . Furthermore, both the expression of exogenous mutants of FOXO1 and the inhibition of AKT led to FOXO1 activation in lymphoma cells, increased binding to MS4A1 promoter and diminished CD20 expression levels. In contrast, a disruption of FOXO1 with CRISPR/Cas9 genome-editing (sgFOXO1) resulted in CD20 upregulation, improved the cytotoxicity induced by rituximab and the survival of mice with sgFOXO1 tumors. Accordingly, pharmacological inhibition of FOXO1 activity in primary samples upregulated surface CD20 levels. Importantly, FOXO1 was required for the downregulation of CD20 levels by the clinically tested inhibitors of BTK, SYK, PI3K and AKT. Taken together, these results indicate for the first time that the AKT-unresponsive mutants of FOXO1 are important determinant of cell response to rituximab-induced cytotoxicity, and suggest that the genetic status of FOXO1 together with its transcriptional activity need further attention while designing anti-CD20 antibodies based regimens for the therapy of pre-selected lymphomas.